2011
DOI: 10.5402/2011/854287
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Panoramic Radiomorphometric Indices of the Mandible in a Brazilian Population

Abstract: The aim of this study was to evaluate radiomorphometric indices in dental panoramic radiographs in order to identify possible interrelationships between these indices and the sex and age of the patients analyzed. The study included 1287 digital panoramic radiographic images of patients that were grouped into five age groups (1 = age 17–20; 2 = age 21–35; 3 = age 36–55; 4 = age 56–69; 5 = over age 70). Two indices—cortical width at the gonion (GI) and below the mental foramen (MI)—were measured bilaterally in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 15 publications
8
32
0
13
Order By: Relevance
“…Quantitative radiomorphometric indices, MI and the GI showed worsening with advancing age, pointing to decreased bone mass. These findings agree with data from studies of several authors [6] [12]- [14].…”
Section: Discussionsupporting
confidence: 82%
“…Quantitative radiomorphometric indices, MI and the GI showed worsening with advancing age, pointing to decreased bone mass. These findings agree with data from studies of several authors [6] [12]- [14].…”
Section: Discussionsupporting
confidence: 82%
“…Horner 2002; Leite et al 2010;Alonso et al 2011;Nagi et al 2014). While other studies have verified that PAM treatment increases BMD in children with OI, our study was intended to analyze mandibular cortical bone changes throughout it, as demonstrated in other bone sites (Zeitlin et al 2003;Rauch et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is one such change that is seen in bones. Osteoporosis is defined as a systemic disease of the bone that is characterized by a reduced bone mass and a disrupted bone tissue microstructure, which lead to increased bone fragility and fracture risk [1][2][3][4]. As it is seldom detected before fractures occur, it is considered to be a silent disease that entails significant social and economic burdens [5].…”
Section: Introductionmentioning
confidence: 99%